Dimensions Of Earnings Management In Transportation Service Companies In Indonesia - Abdul Khalik; Sylvia Sylvia (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
This study examines accounting conservatism, leverage, litigation risk, and financial distress on earnings management. This type of research includes causal research using quantitative methods. The object of this research is a company that publishes audited financial reports and publishes them on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The population of transportation service companies based on the factbook of the Indonesia Stock Exchange in 2020 in 42 companies. In this study, the sampling technique used is purposive sampling. This study uses secondary data collected through the Indonesian stock exchange website and analyzed using Multiple Regression Analysis with the Ordinary Least Square model using the Eviews Version 12 software. The results found that accounting conservatism and leverage significantly affected earnings management. Meanwhile, litigation risk and financial distress have no significant effect on earnings management.